Cartografias da moral e da ética para os dilemas do ciberespaço - Huelsen, Patricia Giannoccaro von (2018)
This study maps the issues found inside of the cyberspace as well as the historical concept of ethics and morality. Within its first section, the main features of the cyberspace and social behaviour in the cyberspace are examined; thoughts and concepts of famous philosophers such as Aristotle, Thomas Aquinas, Kant, Hegel, Durkheim, Weber, Freud e Nietzsche are also discussed. The core objective of this mapping is to understand the dimensions and associations linked to the concept of ethics and morality. It also touches upon key questions such as the notions of: truth, good and evil, moral conscience, beauty as a virtue, as well as ethic, material and aesthetic values. Lastly, a model for analysing these notions and concepts with observations found in the cyberspace is proposed, based on the ideal type model by Max Weber